Relationship of Fine Motor Skills with Vertical Writing Skills at Papandayan Public Elementary School Bogor - Fitri Siti Sundari; Yuli Mulyawati; Tustiyana Windiyani; Eva Mutia (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
This is quantitative research with a correlational study method, with the research title Relationship of Fine Motor Ability as an independent variable and Continuous Writing Skills as a dependent variable. The purpose of this study is to determine the relationship between fine motor skills and the ability to write upright to be connected to the sub-themes of harmonious living at home. The subjects of this study were classes IIA, IIB, IIE, and IIF Papandayan State Elementary School, Bogor Tengah District, Bogor City, Odd Semester of the 2019/2020 Academic Year totaling 104 with a sample of 51 respondents. The data of this study were obtained using the Guttman scale questionnaire using definite choices such as yes or no for fine motor ability variables and using writing test assessments for the variable continuous writing skills. The results showed that there was a positive and significant relationship between fine motor skills and vertical straight writing skills. This is based on statistical analysis which results in a correlation coefficient (rxy) of 0.714 and in the pattern of the problem becomes Ŷ = 39.42 + (0.476x) which means the level of relationship is relatively strong and a tcount of 7.14 is greater than the table with a real level of significance 0.05 of 2,404 and the table with a real level of 0.01 of 1,676 which means significant. Based on the results of this study, it can be concluded that there is a strong, positive and significant relationship between the relationship of fine motor skills with continuous writing skillsKeywords: Fine Motor; Writing Skills Upright.Abstrak Penelitian ini merupakan penelitian kuantitatif dengan metode studi korelasional, dengan judul penelitian Hubungan Kemampuan Motorik Halus sebagai variabel bebas dan Keterampilan Menulis Tegak Bersambung sebagai variabel terikat. Tujuan penelitian ini adalah mengetahui hubungan kemampuan motorik halus dengan keterampilan menulis tegak bersambung pada sub tema hidup rukun di rumah. Subjek penelitian ini adalah kelas IIA, IIB, IIE, dan IIF Sekolah Dasar Negeri Papandayan Kecamatan Bogor Tengah Kota Bogor Semester Ganjil Tahun Pelajaran 2019/2020 berjumlah 104 dengan sampel sebanyak 51 responden. Data penelitian ini diperoleh dengan menggunakan kuisioner skala Guttman menggunakan pilihan yang pasti seperti ya atau tidak untuk variabel kemampuan motorik halus dan menggunakan penilaian tes menulis untuk variabel keterampilan menulis tegak bersambung. Hasil penelitian menunjukkan bahwa terdapat hubungan positif dan signifikan antara kemampuan motorik halus dengan keterampilan menulis tegak bersambung. Hal ini berdasarkan analisis statistik yang menghasilkan koefisien korelasi (rxy) sebesar 0,714 dan dalam pola permasalahannya menjadi Ŷ = 39,42 + (0,476x) yang berarti tingkat hubungan tergolong kuat dan diperoleh thitung sebesar 7,14 lebih besar dari ttabel dengan taraf nyata nyata 0,05 sebesar 2,404 dan ttabel dengan taraf nyata 0,01 sebesar 1,676 yang berarti signifikan. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa terdapat hubungan yang kuat, positif dan signifikan antara hubungan kemampuan motorik halus dengan keterampilan menulis tegak bersambung.Kata Kunci: Motorik Halus; Menulis Tegak Bersambung.